STRATEGI PENGEMBANGAN UMKM MELALUI PEMETAAN GOOGLE MAPS DI DESA SUNGAI SELAN ATAS, KABUPATEN BANGKA TENGAH - Suryadin, Asyraf; Pratama, Julian Rizki; Nur Ulfiyanti, Tania; Rahmini, Rahmi; Febridianti, Chyntia; Sukmawati, Iren; Resparina, Azzati; Nuhaliza, Nuhaliza; Rahilda, Rahilda; Febriansyah, Dany; Miraldy, Muhammad (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2025)
Digitalization of MSMEs in Indonesia, especially in rural areas such as Sungai Selan Atas Village, is a strategic step to increase competitiveness and operational efficiency. Even though MSMEs have a crucial role in the local economy, they still face various challenges in the digitalization process, such as limited technological infrastructure, low digital literacy, and a conventional business culture that is still strong. In this research, a qualitative method with a case study approach was used to analyze the digitalization process of MSMEs in Sungai Selan Atas Village. Through observation, interviews and documentation, data was collected from 19 MSMEs registered in the village. The research results show that the strategy of mapping MSMEs on Google Maps and distributing promotional banners can increase business visibility and accessibility, as well as strengthen networks between MSMEs. Mapping on Google Maps makes it easy for consumers to find the location of MSMEs, even in areas with limited internet connectivity. Meanwhile, promotional banners offer an effective way to attract people's attention without relying on digital technology. Thus, although challenges in digitalization still exist, there are steps that can help MSMEs in Sungai Selan Atas Village to adapt and develop in the digital economy. The successful digitalization of MSMEs in this village will not only increase income and employment, but also contribute to the social and economic welfare of the local community. Therefore, it is important for the government and related parties to continue to support digitalization initiatives, provide digital literacy training, and improve technological infrastructure so that MSMEs can take advantage of the opportunities that exist in this digital era